Prenatal care according to the NOM-007 norm, which relates to maternal morbidity in a health center in San Luis Potosí (2008) - Lucila P. Acosta R; Rosa I. Vega M.; Alicia G. Barron (Universidad de Antioquia, 2012)
Mother and child mortality reflects the level of social and economic development of a country; therefore, reproductive health is a sanitary priority. Mortality prevention depends directly on the coverage and quality of health services. Objective: to assess the compliance of prenatal care with the NOM 007 norm and its correlation with maternal morbidity in a health center located in San Luis Potosí, Mexico. Methodology: a descriptive, correlational, and quantitative study in which the units of analysis were the medical records of 571 pregnant women cared for during 2008. In order to prove the hypothesis, Pearson's r was used. The p value was ≤ 0.05. Results: ages ranged from 13 to 43 years. Additionally, 37.1% of the patients were teenagers and 44.3 % began receiving attention during the second trimester of their pregnancy; 38.2 % attended at least five medical appointments, and 46.4 % had morbidity. For the latter group, urinary infection was the most common condition (224 cases). Prenatal attention was adequate in 2.6 % of the cases according to the actions performed. Health promotion actions were the least frequent. Conclusion: the level of compliance with the NOM 007 norm for prenatal care was considered inadequate in 97.4 % of the cases and was consistent with maternal morbidity (87.5-100 %). This could be related to more frequent appointments for some women and with late treatment, which resulted in less time to perform said actions. Contrary to expectations, greater compliance meant higher maternal morbidity (r = 0.318, p < 0.000).